Importance of nutrition and lifestyle for elderly during the COVID-19 pandemic - Nugroho Abikusno (Jurnal Biomedika dan Kesehatan, 2020)
Presently the world is experiencing a pandemic of a global magnitude never before witnessed and recorded by human civilization. No one is excluded from this disease and the most vulnerable are the very young and/the very old in our population. It is the most highly communicable and severe viral infection and most of our reproductive age population show practically no signs or symptoms of infection unless they are tested positive using the PCR method or arrive at the hospital in acute respiratory distress.(1) The infection spreads mostly in: 1) closed environment with poor ventilation such as clubs, café, restaurants, meeting rooms; 2) among crowds of people such as in public stations, malls, religious gatherings, and cinemas as well as; 3) within close contact with people usually friends, family or co-workers who form the cluster most likely to be infected with the virus.(2)